2022
DOI: 10.12998/wjcc.v10.i23.8170
|View full text |Cite
|
Sign up to set email alerts
|

Role of H2 receptor blocker famotidine over the clinical recovery of COVID-19 patients: A randomized controlled trial

Abstract: BACKGROUND Coronavirus disease 2019 (COVID-19) is a global pandemic putting the population at a high risk of infection-related health hazards, mortality and a potential failure of proper medical therapies. Therefore, it is necessary to evaluate the potential use of the existing drugs that could be used as options for the medical management of COVID-19 patients. AIM To evaluate the role of the H 2 receptor blocker “famotidine” in COVID-19 illne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
1
0
2
Order By: Relevance
“…Se evaluó también el tiempo de estancia hospitalaria, en el que Samimagham, Pahwani y Mohiuddin 24,28,35 evidenciaron una reducción significativa en los días de hospitalización para los pacientes tratados con famotidina. No obstante, la calidad y cantidad de los estudios incluidos no nos permite determinar esta asociación como un resultado confiable, siendo necesario la evaluación posterior con estudios con mayor escala y un diseño sólido.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Se evaluó también el tiempo de estancia hospitalaria, en el que Samimagham, Pahwani y Mohiuddin 24,28,35 evidenciaron una reducción significativa en los días de hospitalización para los pacientes tratados con famotidina. No obstante, la calidad y cantidad de los estudios incluidos no nos permite determinar esta asociación como un resultado confiable, siendo necesario la evaluación posterior con estudios con mayor escala y un diseño sólido.…”
Section: Discussionunclassified
“…La gran expectativa sobre este fármaco llevó a los investigadores a realizar ensayos clínicos aleatorizados, entre ellos uno doble ciego que involucra grandes dosis de famotidina intravenosa en comparación con hidroxicloroquina o remdesivir (NCT04370262) 23 , aunque al momento de la búsqueda solo se han reportado los resultados de mortalidad. Otros ensayos clínicos con altas dosis de famotidina también se están realizando en países como Bangladesh (NCT04504240) e Irán 24,25 .…”
unclassified
“…Famotidine is a histamine 2 receptor antagonist used for decades in the clinic to inhibit gastric acid production. Surprisingly, recent clinical observations, and subsequent clinical trials, revealed that famotidine attenuates the clinical course of COVID-19 [67][68][69][70][71][72]. The mechanism of the famotidine inhibition of cytokine storm was revealed to be by pharmacological stimulation of the vagus nerve inflammatory reflex [73].…”
Section: Famotidinementioning
confidence: 99%